Epidemiological Study of Diabetes Amongst Geriatric Population in An Urban Slum, Nagpur - Singh, JaiPrakash; Saoji, AV; Kasturwar, N B; Pitale, SP; Deoke, AR; Nayse, JG (National Journal of Community Medicine, 2011)
The study was conducted to assess the prevalence and associated risk factors for diabetes in the geriatric population in urban slum areas of Nagpur. A community based cross sectional study was carried out in the field practice area of Urban health training center (UHTC), dept. Of community medicine, NKP Salve Institute of Medical Sciences and Research Center, Nagpur. A total of 400 subjects (165 males and 235 females) aged ≥ 60 years were screened for Diabetes Mellitus. Diagnosis of diabetes mellitus was based on the American Diabetes Association criteria 2004.The data analysis by using Epi Info software. Author observed that prevalence of diabetes was 17.75% and stress was the commonest risk factors 46(64.79%), followed by positive family history of diabetes (63.38%) and others. Family history of diabetes (63.38%) and hypertension 26 (36.62%) were significantly associated with diabetes (p<0.05) while other risk factors were not significantly associated.